The Analysis of the Heavy Metal Iron (Fe), Cadmium (Cd), Copper (Cu) Content In Crystal Guava (Psidium Guajava L.) and Soil at Batu - Hidayati Karamina; Widowati Widowati; Tri Mudjoko (Indonesian Journal of Environment and Sustainable Development, 2019)
Bumiaji region is well-known as it becomes the tourist destination area in Batu City. This area is largely covered by its constant (even below) 20oC temperature along the year in which makes it as the best place to plant horticultural plantation such as Crystal Guava. This plantation is done through careful treatment in applying both organic and inorganic fertilizer and the abundant dose of pesticide continually. These efforts, however, yield some drawbacks to the environment, especially for the soil itself. Thus, this study was aimed for discovering the amount of the heavy metal contained in the soil and Crystal Guava. This study used descriptive analytic method along with using Spectophotometer for testing the heavy metal. The elements of three heavy metal Fe, Cd, Cu in the soil concentration in 30 - 60 cm soil depth were higher than in 0 – 30 cm soil depth. The third content of heavy metals in the soil is included in the high category so that it is harmful to the environment and plants. The heavy metal content of Fe, Cd, Cu in the crystal varieties of guajava fruit in plants aged 5, 6 and 11 years has the results of heavy metal analysis that has exceeded the normal threshold of pollution guidelines.